Hepatitis B virus reverse transcriptase mutations in treatment Naïve chronic hepatitis B patients. Issue 7 (22nd May 2013) - Singla, Bhupesh; Chakraborti, Anuradha; Sharma, Bal Krishan; Kapil, Shweta; Chawla, Yogesh K.; Arora, Sunil K.; Das, Ashim; Dhiman, Radha K.; Duseja, Ajay
Abstract Mutations in the reverse transcriptase (RT) region of the hepatitis B virus (HBV) genome lead to decreased susceptibility to nucleos(t)ide analogs approved for treatment of HBV infection. The aim of this study was to detect and analyze pre‐existing HBV RT mutations in treatment naïve patients with chronic hepatitis B. Seventy one chronic HBV treatment naïve patients were enrolled from January 2009 to June 2011. HBV RT sequence analysis was done by using direct bidirectional sequencing of semi‐nested PCR products. HBV genotypes were determined by multiplex PCR. Genotype D was found in 64 patients (90.1%) followed by genotype C and A which were present in 5 (7.0%) and 2 (2.8%) patients respectively. The results of the RT sequence analysis showed mutations in 34 (47.9%) patients. The rtH248N mutation was the most common mutation, accounting for 47.1% patients. Other common mutations included rtD263E/S, rtM129L, rtF122L/V/I, rtS135Y/H, rtQ149K, rtL91I, rtH126R, rtC256S/G, rtY257W, rtS259T and rtE271D, which were present in 26.5% (9/34), 29.4% (10/34), 20.6% (7/34), 20.6% (7/34), 20.6% (7/34), 17.6% (6/34), 14.7% (5/34), 14.7% (5/34), 11.8% (4/34), 11.8% (4/34) and 11.8% (4/34) patients respectively. The known primary drug resistance mutations were found in 3 (8.8%) patients. The present study shows the presence of RT amino acid substitutions in treatment‐naïve patients with chronic hepatitis B, which may decrease susceptibility to available oral antiviral drugs. On the basis of the finding of this study, genotypic testing is recommended before the start of therapy in naïve patients, so that suitable antiviral drugs can be prescribed. J. Med. Virol. 85:1155–1162, 2013. © 2013 Wiley Periodicals, Inc.